1954
DOI: 10.1104/pp.29.5.473
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis in Chlorella during Intermittent Illumination of Long Periodicity

Abstract: Subsequent to a dark period of several minutes the rate of photosynthesis during the first seconds of illumination is generally less than that in the subsequent steady state. This phenomenon has been described by the general term "induction." Recently, Burk and Warburg (1), using a manometric method, determined pressure changes during light and dark for a suspension of Chlorella which was illuminated for periods of three minutes or less alternated with equal dark periods. The pressure changes were interpreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1955
1955
1960
1960

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Hence other workers chose to investigate this problem using a variety of methods. Further studies have been made by Brackett et al (1953) using a polarographic method, by Hill & Whittingham( 1953) and Whittingham( 1954) showed a marked increase in rate of oxygen consumption during the first 10-20 sec. darkness, as compared to the rate in the steady state, whether the dark period followed a light period of 3 or 6 min.…”
Section: ( 2 ) Respiration During a Non-steady State Of Photosynthesismentioning
confidence: 65%
See 4 more Smart Citations
“…Hence other workers chose to investigate this problem using a variety of methods. Further studies have been made by Brackett et al (1953) using a polarographic method, by Hill & Whittingham( 1953) and Whittingham( 1954) showed a marked increase in rate of oxygen consumption during the first 10-20 sec. darkness, as compared to the rate in the steady state, whether the dark period followed a light period of 3 or 6 min.…”
Section: ( 2 ) Respiration During a Non-steady State Of Photosynthesismentioning
confidence: 65%
“…The experiments of Hill et al and the majority of those of Damaschke et al were confined to Observations in the presence of an oxygen concentration of between 0.1 and 3.0%. Whittingham (1954) found that after periods of one minute illumination the initial rate of oxygen consumption was sometimes greater than the subsequent steady dark rate; when present the effect could be repeated for a number of cycles of light and dark. T h e half-time of decay was of the order of 2 min.…”
Section: ( 2 ) Respiration During a Non-steady State Of Photosynthesismentioning
confidence: 97%
See 3 more Smart Citations